Model development for web - atlas system applying in administration management - Quy, Bui Ngoc (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 1, 2012)
Abstract. Traditionally, the maps are very important tools in government management and decision making. Nowadays, information technologies blooming as well as wide spreaded of internet involve the evolution in cartography technologies. The combining of cartography and internet creating new map generation - web maps. This new maps allow users see and apply it in any place which have internet connection. Web maps have many advences over traditional maps. Therefore, there are many researcher applying them in socio-economical and culture aspecs. This paper describes research results in development of a model for web atlas applying in administration management inHanoi,Vietnam. Keywords: Webatlas, Web Map, Electronic Atlas, Internet map, Administration management.